A Study in respect of the delay in the cases pending under Revenue Laws in Gujarat - Raval, Prakash Kuamr G (Indian Journal of Community Health, 2025)
The study examines delays in resolving revenue cases under Gujarat's land laws. Historically, India's agrarian economy relied heavily on agriculture, with various land revenue codes enforced over time, including the Bombay Land Revenue Code (1879). After Gujarat’s formation in 1960, no significant reforms were made to these laws, resulting in protracted litigation. Disputes often span decades, burdening farmers and causing generational involvement in cases. Key land disputes involve issues like mutation entries, hereditary transfers, and acquisition for infrastructure projects. The judicial hierarchy—from Mamlatdars to Deputy Collectors, Collectors, Revenue Secretaries, and eventually civil or high courts—entails complex, time-consuming appeals and revisions. Cases often get remanded for reconsideration, further prolonging resolution. To address these inefficiencies, the study advocates for establishing district-level revenue tribunals, replacing the current multi-tiered system. These tribunals would streamline dispute resolution, reduce appeal stages, and ensure quicker justice. Chaired by retired judges with revenue officers as members, tribunals could alleviate workloads for existing revenue officials, curbing corruption and delays. The Gujarat Revenue Tribunal Act, 1957, should be amended, incorporating sections from the Revenue Code to enhance judicial efficiency. This reform would benefit stakeholders by expediting decisions and improving agricultural land governance.